Delay of cell growth and loss of stemness by inhibition of reverse transcription in human mesenchymal stem cells derived from dental tissue. Issue 5 (3rd September 2019) - Lee, Won-Cheol; Kim, Dae-Young; Kim, Mi-Jeong; Lee, Hyeon-Jeong; Bharti, Dinesh; Lee, Sung-Ho; Kang, Young-Hoon; Rho, Gyu-Jin; Jeon, Byeong-Gyun
ABSTRACT: The present study investigated the cellular properties in the dental tissue-derived mesenchymal stem cells (DSCs) exposed to nevirapine (NVP), an inhibitor of reverse transcriptase (RTase). After a prolonged exposure of DSCs for 2 weeks, the population doubling time (PDT) was significantly ( P < .05) increased by delayed cell growth in the DSCs treated with 250 and 500 μM NVP, compared with untreated DSCs. Furthermore, the G1 phase of cell cycle with high activity of senescence-associated β-galactosidase was also significantly ( P < .05) increased in the 250 μM NVP-treated DSCs, compared with untreated DSCs. The level of telomerase activity was unchanged between control and treatment. However, following the treatment of NVP, negative surface markers for mesenchymal stem cells (MSCs), such as CD34 and CD45, were significantly ( P < .05) increased, while positive surface markers for MSCs, such as CD90 and CD105, were significantly ( P < .05) decreased in the NVP-treated DSCs than those of untreated DSCs. Furthermore, the differentiation capacity into mesodermal lineage was gradually decreased, and a significant ( P < .05) decrease of expression level of NANOG, OCT-4 and SOX-2 transcripts was observed in the DSCs treated with NVP, compared with untreated control DSCs. Taken together, the present results have revealed that inhibition of RTase by NVP induces delayed cell growth and loss of stemness.